202k views
8 votes
Please help me ASAP!!

Please help me ASAP!!-example-1

2 Answers

5 votes

Answer:

Explanation:

7z^2 + 8z + 3 = 3z^2

4z^2 + 8z + 3 = 0

(2z + 3)(2z + 1) = 0

2z + 3 = 0

z = -3/2

2z + 1 = 0

z = -1/2

User Guido
by
4.5k points
9 votes

Answer:

z=(-3/2, -1/2) (Or z=(-1.5,-0.5) if they want decimals instead of fractions)

Explanation:

7z²+8z+3-3z²=0

4z²+8z+3=0

(2z+3)(2z+1)=0

z=(-3/2, -1/2) (Or z=(-1.5,-0.5) if they want decimals instead of fractions)

User Enoc
by
5.0k points